Improvement Students' Understanding through Problem Based Learning - Ranggih Meira Putri Kharisma (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to improve grade X students' understanding of environmental pollution concepts by applying the Problem-Based Learning (PBL) model at Islamic Senior High School Ghozaliyah. Using an experimental design with a quantitative approach, the research employed a One Group Pre-test Post-test Design. The subjects were 30 grade X students at Islamic Senior High School Ghozaliyah. Data were collected through concept understanding tests administered in two phases: pre-test before treatment and post-test after treatment. The data analysis employed descriptive statistical methods to describe the students' learning outcomes and compared pre-test and post-test scores to measure improvement. The results showed an improvement in students' understanding of environmental pollution concepts after implementing the Problem-Based Learning model. This is evident from the lower average pre-test scores compared to the higher post-test scores and the significant improvement in N-Gain. This research is expected to contribute to developing effective learning models to enhance environmental concept understanding in schools.